The birth of the Caribbean Society of Endoscopic Surgeons-A historical article-. (February 2019) - Rosin, David; Fa Si Oen, Patrick
Abstract: The Caribbean Society of Endoscopic Surgeons (CaSES) is a regional surgical organization that acts as a quality-enhancing body for the Caribbean region. It does so through many activities including an annual regional meeting. In this historical article, the history, purpose and future developments of the organization is outlined.